An analysis of the differences in efficiency of man-up in water polo according to the speed of realization - Hraste, M. (Acta Kinesiologica, 2018)
The scope of this research is the identification and the explanation of differences of three levels of water polo players in some parameters of man-up efficiency. Using the Kruskal-Wallis test and multiple comparisons of mean ranks for all groups atthe significance level of a=0.05, the hypothesis that there are significant differences between three levels of water polo players in four of the fifteen variables of man-up efficiency in water polo was confirmed. The results indicate that high quality teams are dominated in medium-speed realization because it is very probably they need less time to find the optimal situation for realizing the man-up situation than the medium and low quality teams. There is a reasonable possibility that the differences are probably caused by the degree of learned and implemented tactical knowledge, the degree of scoring ability and the best selectionforcertain rolesin the team